2010
DOI: 10.1111/j.1469-0691.2009.02926.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of bacteraemia or fungaemia after removal of colonized central venous catheters in patients with negative concomitant blood cultures

Abstract: There are limited data on the clinical significance of positive central venous catheter (CVC) tip cultures associated with concomitant negative blood cultures performed at the time of CVC removal. A retrospective cohort study of all patients who yielded isolated positive CVC tip cultures was conducted in a tertiary-care hospital with 2200 beds during a 10-year period. All patients with isolated positive CVC tip cultures were observed for the development of subsequent bacteraemia or fungaemia between 2 and 28 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 11 publications
2
18
0
1
Order By: Relevance
“…In hospitalized patients with a bacterial culture positive intravenous catheter, 61% had a concomitant bacterial infection. (46) Injection equipment prepared for reuse by boiling is frequently culture positive (e.g., 33% contamination rate in one assay in Tanzania), and by implication injection equipment reused without sterilization is likely to be infectious. (47) In countries with a low prevalence of blood-borne viruses, the primary benefit of preventing injection equipment reuse may be the prevention of potentially serious bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…In hospitalized patients with a bacterial culture positive intravenous catheter, 61% had a concomitant bacterial infection. (46) Injection equipment prepared for reuse by boiling is frequently culture positive (e.g., 33% contamination rate in one assay in Tanzania), and by implication injection equipment reused without sterilization is likely to be infectious. (47) In countries with a low prevalence of blood-borne viruses, the primary benefit of preventing injection equipment reuse may be the prevention of potentially serious bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al . [8] recently showed that bloodstream infection was rare subsequent to the removal of colonized central venous catheters in patients with negative concomitant blood cultures. In his study, most patients with catheter‐related S. aureus bacteraemia had positive blood cultures before the tip result was available and only two patients of the 58 with S. aureus isolated from the central venous catheter tip culture developed subsequent bacteraemia (3.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Park et al [8] recently showed that bloodstream infection was rare subsequent to the removal of colonized central venous catheters in patients with negative concomitant blood cultures. In his study, most patients with catheter-related [4].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study [63] on 312 patients with a positive catheter culture and a negative blood culture, only eight patients (2.6%) subsequently developed CRBSI with the same germ as the one cultured from the tip, suggesting a low yield for this costly and time-consuming strategy.…”
Section: Diagnosis: Cultures Of Intravenous Cathetermentioning
confidence: 99%